Transportation of Food by Cold Chain Methods one of the Cause of Reoccurrence Covid-19 Infection during its Pandemic - Mesut Selamoğlu; Ali Raza Memon (Turkish Journal of Agriculture: Food Science and Technology)
The Corona Virus is the pandemic all over the world. This viral infection attacked all over the world like as disaster of viral infection which causes morbidity and mortality in different regions of world like Asia, Europe, and Africa etc. The different countries control the spread and complications of covid-19 like Acute Respiratory Distress Syndrome in well manner. In second wave there was again out break of covid-19 some regions of world. Here we discuss the causes of reoccurrence and their preventive measurements from our break effects of Covid-19.